Evaluation of Nutritional Awareness, Hygiene Practices, and Lifestyle Factors on Health Outcomes and Academic Concentration Among Tertiary Level Students in Chattogram, Bangladesh - Zarin Tasnim; Md. Mazharul Alam; Mehnaz Mashuk Prima; Tajwar Karim; Abdur Rahman (Health Dynamics, 2026)
Background: Nutritional habits, hygiene practices, and lifestyle attitudes are recognized as important decisive factors of health and academic performance among university students. However, available literature from developing countries, particularly Bangladesh, remains limited. This study aimed to evaluate the relationship between nutritional awareness, hygiene practices, lifestyle factors, and their effects on health outcomes and academic concentration among tertiary-level students in Chattogram City, Bangladesh. Methods: A cross-sectional study was conducted among 93 tertiary-level students selected through convenience sampling. Data were collected using a structured questionnaire covering demographic characteristics, dietary habits, hygiene practices, lifestyle factors, and academic performance indicators. Composite scores for hygiene and nutrition were generated by converting ordinal variables into numerical scales. Descriptive statistics (mean ± standard deviation) were calculated, followed by correlation analysis and multiple linear regression to assess associations between independent variables and outcomes like academic concentration and grade point average (GPA). Results: The mean age of participants was 20.51 ± 1.74 years. The average sleep duration, screen time, GPA, and academic concentration scores were 6.66 ± 0.91 hours, 5.39 ± 2.17 hours, 3.41 ± 0.42, and 6.58 ± 1.60, respectively. Correlation analysis showed weak relationships among variables, with sleep duration showing a weak positive association with academic concentration (r = 0.14) and GPA (r = 0.08), while screen time revealed a weak negative correlation with GPA (r = -0.07). Regression analysis pointed out that none of the examined factors were statistically significant (p > 0.05). Conclusions:The findings suggest that individual lifestyle, nutritional, and hygiene factors have limited independent influence on academic performance and concentration among students. Academic success cannot be explained by some specific lifestyle variables in isolation, but rather through complex interactions among multiple determinants.  Future studies with larger sample sizes and longitudinal designs are recommended to better understand these relationships.